The evolution of monogamy in cichlids and marine reef fishes - Stanbrook, Emily; Fitzpatrick, John L.; Balshine, Sigal; Shultz, Susanne (Frontiers in Ecology and Evolution, 2022)
Although several hypotheses have been proposed to explain the emergence of social monogamy, its origin is still intensely debated. Monogamy has many potential drivers, but evolutionary causality among them remains unclear. Using phylogenetic comparative methods within a Bayesian framework we explored the evolution of monogamy in cichlids and in marine reef fishes because, while both groups are characterised by unusually high incidence of social monogamy, they face very different ecological challenges. For each group, we examined four classic hypotheses that explain the evolution of monogamy: female dispersal, male mate guarding, female-female intolerance, and the biparental care hypotheses. We also explored whether the ecological traits of diet and shelter use are evolutionarily coupled with these hypotheses or with monogamy. First, we found that the evolution of monogamy was predicted by male territoriality in cichlids and simultaneous male and female territoriality in marine reef fishes. We suggest that these results provide support for the male mate guarding hypothesis in cichlids and female-female intolerance hypothesis in marine reef fishes. Second, we demonstrate clear evidence against the biparental care hypothesis, as biparental care was a consequence, not a cause, of monogamy in our analyses. Third, as female dispersal drove the loss of monogamy in both cichlids and marine reef fishes, this suggests the female dispersal hypothesis is not driving the evolution of monogamy in either group. These findings in two highly-monogamous fish taxa largely support prior findings from primate and bird comparative studies and provide novel large-scale evidence for a link between mate guarding and the evolution of monogamy.